Application of gold-containing nanomaterial as SERS (Surface Enhanced Raman Scattering) substrate or biosensor in myocardial infarction marker recognition

By using gold-containing nanomaterials of different structures as SERS substrates or biosensors, the identification of myocardial infarction markers cTnI and miRNA-133a is solved in the prior art for detecting height limit, insufficient selectivity, high cost and poor spectral stability. Problem, high sensitivity, low cost and stable detection of myocardial infarction markers has been achieved.

CN119438177APending Publication Date: 2025-02-14SHANGHAI CHEST HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714143.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing precious metal nanomaterials have problems such as high detection limits, insufficient selective identification, high cost and poor spectral stability in detecting markers of myocardial infarction.

Method used

Use gold nanomaterials as SERS substrates or biosensors to identify the myocardial infarction markers cTnI and the combination of different structures and carriers (such as gold nanostar particles, core-shell structures, loaded transition metal oxides and Raman signaling molecules, etc.) miRNA-133a.

Benefits of technology

The detection of myocardial infarction marker with low detection limit and good stability is achieved, which improves the selectivity and sensitivity of detection, reduces costs, and enhances spectral stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438177A_ABST
    Figure CN119438177A_ABST
Patent Text Reader

Abstract

The invention provides an application of a gold-containing nano-material as an SERS (Surface Enhanced Raman Scattering) substrate or a biosensor in identifying myocardial infarction markers or manufacturing myocardial infarction marker detection equipment / device. The application is characterized in that the Au-containing nano-material is selected from at least one of the following components: A, gold nano-star particles AuNSs; b, a core-shell structure AuNSs (at) Ag of silver is coated outside the gold nano star particles; c, transition metal oxide loaded with A or B; d, A, B or C loaded with Raman signal molecules; e, D of which the surface is bound with an antibody and / or a capture probe; f. E bound with an antigen, and / or miRNA; and G, A-F oxidized and activated by hydrogen peroxide and TMB. Based on the local surface plasma resonance characteristic of precious metal and in combination with a transition metal oxide nano-enzyme material, through the synergistic effect of an electromagnetic field enhancement mechanism and a chemical enhancement mechanism, the SERS nano-enzyme biological detection substrate for efficient detection of the AMI marker is developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to biological detection technology, specifically, to a detection technology of myocardial infarction markers, and more specifically, to an application of a gold-containing nanomaterial as a SERS substrate or a biosensor in identifying myocardial infarction markers or manufacturing myocardial infarction marker detection equipment / devices. Background Art

[0002] In the past few decades, although noble metal nanoparticles have many advantages as SERS substrates for detecting AMI, precise control of particle shape, size, stability, biocompatibility and other issues still pose great challenges to improving SERS signals.

[0003] Although noble metal nanomaterials can achieve ultra-high SERS enhancement due to surface plasmon resonance in the visible light region, noble metal substrates are insufficient in selective recognition of target molecules, and their high cost and poor spectral stability have severely restricted their development in practical applications.

[0004] In addition, the technologies currently used in the field of myocardial infarction marker identification generally have the problem of high detection limits. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned defects and provide a SERS substrate or biosensor with low detection limit and good stability.

[0006] The present invention provides an application of a gold-containing nanomaterial as a SERS substrate or a biosensor in identifying myocardial infarction markers or manufacturing a myocardial infarction marker detection device / apparatus, characterized in that:

[0007] The Au-containing nanomaterial is selected from at least one of the following A to F:

[0008] A. Gold nanostar particles Au NSs;

[0009] B. Au NSs@Ag core-shell structure of gold nanostar particles coated with silver;

[0010] C. Transition metal oxide loaded with A or B;

[0011] D. A, B or C loaded with Raman signal molecules;

[0012] E. D having antibodies and / or capture probes bound to the surface;

[0013] F. E bound to antigen and / or miRNA;

[0014] G. AF activated by oxidation with hydrogen peroxide and TMB.

[0015] Furthermore, the application provided by the present invention is also characterized in that:

[0016] The above-mentioned myocardial infarction markers include at least one of cTn I and miRNA-133a.

[0017] Furthermore, the application provided by the present invention is also characterized in that:

[0018] The gold-containing nanomaterials described above recognize myocardial infarction markers in ex vivo serum samples.

[0019] Furthermore, the application provided by the present invention is also characterized in that:

[0020] The preparation method of the above-mentioned gold nanostar particles Au NSs is as follows: sodium citrate solution is added to HAuCl4 solution, and after reacting until gold nanospheres Au NPs are formed, water, HAuCl4 and HCl, AgNO3 and ascorbic acid are added thereto, and after reacting until the solution turns blue-black, stirring is continued for 10-20 minutes to obtain the desired Au NSs solution.

[0021] Furthermore, the application provided by the present invention is also characterized in that:

[0022] The above-mentioned gold nanostar particles coated with silver core-shell structure Au NSs@Ag are synthesized by a seed-mediated method: after preparing a gold nanostar particle solution using a gold nanosphere Au NPs seed solution, ascorbic acid is used to reduce the silver nanoparticles to the surface of the gold nanostars to prepare Au NSs@Ag.

[0023] Furthermore, the application provided by the present invention is also characterized in that:

[0024] The above transition metal oxide is selected from MoO2.

[0025] Furthermore, the application provided by the present invention is also characterized in that:

[0026] The preparation method of the transition metal oxide loaded with A or B is as follows: under stirring, HAuCl4 and HCl, AgNO3 and ascorbic acid are added in sequence to the mixture of Au NPs seed solution and MoO2 until the solution turns blue-black, and stirring is continued for 1-3 hours.

[0027] Furthermore, the application provided by the present invention is also characterized in that:

[0028] The above-mentioned loaded Raman signal molecules are selected from 4-MBA and DTNB.

[0029] Furthermore, the application provided by the present invention is also characterized in that:

[0030] The capture probe is an amino-modified capture probe.

[0031] Furthermore, the application provided by the present invention is also characterized in that:

[0032] In the above-mentioned preparation process of AF activated by oxidation with hydrogen peroxide and TMB, the volume ratio of AF, TMB and H2O2 is 1:3-5:2-4, and the reaction time is 5-15min. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 .Schematic diagram of the preparation of Au NSs@Ag;

[0034] Figure 2 . The particle size results of different dosages of AgNO3, where a is 0uL, b is 100uL, c is 300uL, d is 500uL, e is 700uL, and f is a line graph of different dosages of AgNO3;

[0035] Figure 3 .Raman spectra of different dosages of AgNO3;

[0036] Figure 4 .Schematic diagram of Au NSs@Ag SERS substrate for detecting cTn I and miRNA-133a;

[0037] Figure 5 .Raman images of Au NSs@Ag, including: (a) Raman optical microscopy image of Au NSs@Ag; (b) 2D Raman imaging image of Au NSs@Ag; (c) 3D Raman spectrum of Au NSs@Ag nanotag;

[0038] Figure 6 Comparison results of cTn I at different concentrations, including (a) Raman spectra of cTn I standard samples at different concentrations; (b) Raman intensity standard error statistical histogram of cTn I at different concentrations; (c) The linear relationship between cTn I concentration and Raman intensity in standard PBS environment (red line) and real serum environment (blue line); (d) Raman response selectivity diagram of different biomarkers (10 ng·mL-1) to SERS nanotags;

[0039] Figure 7 Comparison results of miRNA-133a at different concentrations, including: (a) Raman spectra of miRNA-133a standard samples at different concentrations; (b) Raman intensity standard error statistical histogram of miRNA-133a at different concentrations; (c) The linear relationship between miRNA-133a concentration and Raman intensity in the standard miRNA-133a environment (red line) and the real serum environment (blue line); (d) Raman response of different biomarkers to SERS nanotags;

[0040] Figure 8 .In the standard PBS environment, the standard samples of Au NSs@Ag-4-MBA and Au NSs@Ag-DTNB were tested under 532nm and 633nm lasers, respectively, including: (a) Raman spectrum of Au NSs@Ag-4-MBA under 530nm laser; (b) Raman spectrum of Au NSs@Ag-4-MBA under 633nm laser; (c) Raman spectrum of Au NSs@Ag-DTNB under 530nm laser; (d) Raman spectrum of Au NSs@Ag-DTNB under 633nm laser;

[0041] Fig. 9 .COMSOL simulation results, including (a) electromagnetic field distribution around a single Au NSs@Ag; (b) electromagnetic field distribution around multiple Au NSs@Ag core-shell structures; (c) local magnification of Figure (b) (532nm);

[0042] Fig.10 .COMSOL simulation results, including (a) electromagnetic field distribution around a single Au NSs@Ag; (b) electromagnetic field distribution around multiple AuNSs@Ag core-shell structures; (c) local magnification of (b) (633nm)

[0043] Fig.11 .Study on the activity of Au NSs nanozymes and Au NSs@Ag nanozymes, including: (a) photos of Au NSs (left) and AuNSs@Ag (right); (b) Raman spectra detected by 4-MBA; (c) statistical histogram of Raman intensity standard error; (d) photos of Au NSs nanozymes (left) and Au NSs@Ag nanozymes (right); (e) Raman spectra of the two nanozymes; (f) statistical histogram of Raman intensity standard error of the two nanozymes;

[0044] Fig.12 .Stability study, including: (a) Au NSs@Ag stability study; (b) Au NSs nanozyme stability study;

[0045] Fig.13 .Schematic diagram of the preparation of MoO2@Au NSs composite materials;

[0046] Fig.14 .SEM images of @Au NSs prepared from different transition metal oxides, including (a) SEM image of CeO2@Au NSs, (b) SEM image of MnO2@Au NSs, and (c) SEM image of MoO2@Au NSs;

[0047] Fig.15. Raman spectra and Raman intensity histograms of different materials composited with Au NSs, including: (a) CeO2 Raman; (b) MnO2 Raman; (c) MoO2 Raman; (d) CeO2 histogram; (e) MnO2 histogram; (f) MoO2 histogram;

[0048] Fig.16 .XPS spectra of MoO2@Au composite materials, including (a) full spectrum, (b) Mo 3d, (c) Au 4f, and (d) high-resolution XPS spectra of O 1s;

[0049] Fig.17 .Peroxidase reaction mechanism diagram of MoO2@Au NSs;

[0050] Fig.18 .Schematic diagram of the peroxidase reaction of MoO2@Au NSs under 633nm laser excitation;

[0051] Fig.19 . The results of studying the activity of nanozymes using Raman laser spectrometer, including (a) schematic diagram of the peroxidase reaction of MoO2@Au NSs under 633nm laser excitation; (b) statistical histogram of the standard error of Raman intensity;

[0052] Fig. 20 .Some comparative experiments were carried out using UV-visible spectrophotometer to study its catalytic performance, including: (a) physical picture of MoO2@Au NSs nanozymes at different concentrations; (b) relationship between different concentrations of MoO2@Au NSs and nanozyme activity; (c) relationship between different concentrations of TMB and nanozyme activity; (d) relationship between different concentrations of H2O2 and nanozyme activity; (e) relationship between pH value and nanozyme activity; (f) relationship between reaction time and nanozyme activity;

[0053] Fig.21 .The uniformity of the surface morphology and SERS signal of MoO2@Au NSs, including (a) 2D Raman imaging of MoO2@Au NSs; (b) 3D Raman spectrum of MoO2@Au NSs nanotags;

[0054] Fig. 22 .Evaluation of the sensitivity of MoO2@Au NSs nanolabels, including: (a) Raman spectra of standard cTn I samples with different concentrations on MoO2@Au NSs; (b) Raman intensity standard error statistical histogram of cTn I with different concentrations; (c) Linear relationship between cTn I concentration and Raman intensity in a standard PBS environment; (d) Linear relationship between cTn I concentration and Raman intensity in a real serum environment;

[0055] Fig.23.The stability and specificity results of MoO2@Au NSs nanotags for cTn I, including (a) MoO2@AuNSs stability detection; (b) Raman response of different biomarkers to SERS nanotags;

[0056] Fig.24 .Mechanism of the enzyme activity of MoO2@Au NSs, including: (a) standard curve of TMB concentration; (b) relationship between reaction rate and TMB concentration; (c) Michaelis-Menten curve of peroxidase activity of MoO2@Au NSs with TMB as substrate; (d) standard curve of H2O2 concentration; (e) relationship between reaction rate and H2O2 concentration; (f) Michaelis-Menten curve of peroxidase activity of MoO2@Au NSs with H2O2 as substrate; DETAILED DESCRIPTION

[0057] The present invention is capable of various modifications and various embodiments, and therefore specific embodiments are illustrated and described in the accompanying drawings. However, this is not intended to limit the present invention to specific implementations, but should be understood to include all modifications, equivalents, and even substitutes that fall within the concept and technical scope of the present invention.

[0058] Example 1. Preparation of AuNSs@Ag core-shell structure SERS substrate and detection of myocardial infarction markers

[0059] 1. Preparation of Au NSs@Ag core-shell structure

[0060] like Figure 1 As shown, Au NSs@Ag was synthesized by a seed-mediated method, that is, after a gold nanostar particle solution was prepared using a gold nanosphere seed solution, ascorbic acid was used to reduce silver nanoparticles to the surface of the gold nanostars to prepare Au NSs@Ag.

[0061] Specifically, first, 50 mL of 0.01 wt.% HAuCl4 solution was added to a round-bottom flask. Then, after heating the solution in an oil bath to boil, 1.0 mL of 0.01 wt.% sodium citrate solution was quickly added under magnetic stirring. After 30 min of reaction, the solution was observed to turn wine red, proving the formation of gold nanospheres. In the second step, 25 mL of deionized water and 2 mL of the previously prepared gold nanosphere seed solution were added to a clean beaker. Under magnetic stirring, 0.5 mL of 0.025 M HAuCl4 and 50 μL of 1 M HCl were added in sequence. After the mixture was stirred for about 3 min, 0.5 mL of 0.002 M AgNO3 and 0.25 mL of 0.1 M ascorbic acid were added. During this process, the color of the solution quickly changed from light yellow to blue-black. Stirring was continued for about 10 min to obtain the desired Au NSs solution. Finally, 40 mL of deionized water and 2 mL of Au NSs were added to the round-bottom flask. Then, 2 mL of 0.01 wt.% sodium citrate and 2 mL of 0.01 M ascorbic acid were added in sequence, while maintaining magnetic stirring at 750 rpm. In the subsequent step, 0.01 M AgNO3 was slowly added dropwise at a rate of 4 mL / h using a medical automatic syringe pump (the results of different amounts of AgNO3 are shown in Table 1). Figure 2 and 3 As shown in the figure, in the experimental conditions of AuNSs@Ag, the effect of 0μL, 100μL, 300μL, 500μL, and 700μL silver nitrate solution on the thickness of the core-shell structure was studied and the Raman performance of the core-shell structure at different thicknesses was tested to obtain the Au NSs@Ag (500μL) with the best SERS performance, that is, under the same concentration of ascorbic acid and nitrate, the volume ratio was 1:0.05-0.35, and the optimal ratio was 1:0.25). During this process, the color of the solution gradually transitioned from colorless to orange, and finally formed a light yellow solution. The obtained Au NSs@Ag core-shell structure was stored at 4°C for further characterization and application.

[0062] 2. Preparation of Au NSs@4-MBA@Ag

[0063] First, 2 mL of Au NSs seed solution was introduced into 10 mL of a solution containing 0.1 M hexadecyltrimethylammonium chloride (CTAC), and then sonicated for 5 min. Subsequently, 50 μL of 0.06 M 4-MBA ethanol solution was added to the mixture, and the resulting suspension was sonicated for 30 min. Next, 1 mL of 0.04 M ascorbic acid solution and 1 mL of 0.01 MAgNO3 aqueous solution were added to the reaction mixture, and sonication was continued for 60 min. After the sonication was completed, the reaction mixture was centrifuged at 10,000 rpm for 10 min. The resulting precipitate was centrifuged 2-3 times with water. Finally, the purified nanoparticles were redispersed in 10 mL of water for further analysis and application.

[0064] 3. Preparation of Nanotags

[0065] Preparation of cTn I Raman label: First, take 2 mL of the above solution, add 100 μL of 500 μM COOH-PEG-SH solution to the mixture, then stir to ensure uniformity, and incubate the resulting mixture at 4 ° C overnight. Then, add 5 μL of 40 mg / mL EDC solution and 110 mg / mL NHS solution to activate the functional groups. After gently stirring the reaction in the dark for 15 minutes, add 10 μL of 0.1 mg / mL antibody solution, and incubate the mixture at 4 ° C overnight to promote antibody binding. After antibody binding, add 10 μL of 1.0 mg·mL -1 BSA solution. The reaction was carried out at 37°C for 1 h to block any unbound sites.

[0066] Preparation of miRNA-133a Raman tag: First, 1 mL of the prepared Au NSs@Ag solution was transferred to a 5 mL centrifuge tube, and then 100 μL of 0.01 M freshly prepared thiosulfate (DTNB) ethanol solution was added. DTNB binds by forming Au-S covalent bonds. The mixed solution was placed on a vortexer and vortexed for 30 seconds before incubating the mixed solution in an oven at 37°C for 2 hours. Then, the mixture was centrifuged at 7500 rpm for 6 minutes to remove excess DTNB. The precipitate was resuspended in 1 mL of MES buffer. 1 mL of Au NSs@Ag@DTNB was mixed with 20 μL of 5 mg / mL LEDC aqueous solution and reacted in a shaker under light-proof conditions for 20 minutes to activate the carboxyl groups on DTNB. Subsequently, 100 μL of amino-modified capture probe was added, which can bind to DTNB through the condensation reaction of amino and carboxyl groups. After shaking for 2 h on a shaker, 10 μL of 2% BSA was added to block unbound carboxyl groups. Blocking was performed in an oven at 37°C for 1 h. Purification was performed by 2-3 centrifugation, and the nanotags were resuspended in 1 mL of DEPC water at 4°C until use.

[0067] 4. Performance Testing

[0068] SERS performance test of cTn I: (1) SERS substrate test: Take 10μL sample solution in the groove of the slide, place it in a 37℃ oven for reaction for 15 minutes until a uniform film is formed on the surface, and then quickly perform Raman test; (2) Standard PBS environment test: Add 10μL Au NSs@4-MBA@Ag nanotag and 10μL cTn I in different concentrations of standard PBS environment to the groove of the slide, ensure that there are no bubbles and the sample is uniform, and react at 37℃ for 15 minutes to form a uniform film on the surface, and finally perform Raman test. (3) Real serum test: Add 10μL Au NSs@4-MBA@Ag nanotag and 10μL cTn I in different concentrations of real human serum to the groove of the slide, ensure that there are no bubbles and the sample is uniform, and react at 37℃ for 15 minutes to form a uniform film on the surface, and finally perform Raman test. The wave number test range during the experiment is 500-2000cm -1 , laser wavelength: 633nm, laser power is 1mW, and cumulative time is 10s.

[0069] SERS performance test of miRNA-133a: (1) Standard PBS environment test: Add 10μL Au NSs@DTNB@Ag nanotags and 10μL miRNA-133a samples of different concentrations in a standard DEPC environment into the groove of the glass slide, ensure that there are no bubbles and the sample is uniform, and react at 37°C for 15 minutes to form a uniform film on the surface, and finally perform Raman test. (2) Real serum test: Add 10μL Au NSs@DTNB@Ag nanotags and 10μL real patient serum samples of different concentrations into the groove of the glass slide, ensure that there are no bubbles and the sample is uniform, and react at 37°C for 15 minutes to form a uniform film on the surface, and finally perform Raman test. The wave number test range during the experiment was 500-2000cm -1 , laser wavelength: 633nm, laser power is 1mW, and cumulative time is 10s.

[0070] 5. Results and Discussion

[0071] 5.1. Detection of myocardial infarction markers using Au NSs@Ag SERS substrate

[0072] like Figure 4 As shown, the designed gold nanostar core-shell structure is used to detect miRNA-133a while detecting cTn I, thereby achieving mutual calibration and improving accuracy.

[0073] 5.1.1 Detection of cTn I using Au NSs@Ag SERS substrate

[0074] like Figure 5 As shown, the surface uniformity of the Au NSs@Ag substrate material was studied using laser Raman microscopy. Figure 5 The Raman mapping in b is consistent with the uniform morphology observed by Raman laser microscopy (e.g. Figure 5 a), which reflects the excellent signal uniformity and consistency of Au NSs@Ag material as SERS substrate. Figure 5 c It can also be seen that the overall SERS performance of the material surface is consistent and stable.

[0075] like Figure 6 As shown in Figure 1, the performance of Au NSs@Ag material in detecting biomarker cTn I was studied. First, a series of cTn I concentrations (0-10 ng / mL) were prepared in a PBS environment and then Raman detection was performed. As the cTn I concentration increased from 0 ng / mL to 10 ng / mL, the SERS signal gradually increased, as shown in Figure 1. Figure 6 a and Figure 6 b. It is worth noting that Figure 6 As shown by the red line in c, the Raman signal under standard PBS environment is linearly related to the cTn I concentration and the resulting equation is I = 2905.49*X + 7597.05 (R 2 =0.998) and the detection limit was calculated to be 0.003 ng / mL. On the other hand, real serum samples from 10 MI patients were tested, such as Figure 6 As shown by the blue line in c, it was found that among the results of many serum samples, the concentration of cTn I antigen showed a good linear relationship with the SERS signal. In the real human serum environment, the linear relationship between cTn I concentration and SERS intensity is I = 2079.079*X + 5640.434, with a linear correlation coefficient of 0.988 and a LOD of 0.005ng / mL. More importantly, we found that the two linear relationship curves obtained in the standard PBS environment and the real human serum environment are roughly consistent, which is mainly attributed to the high stability of Au NSs@Ag and the reasonable core-shell structure design. In addition, we performed specific detection on the Au NSs@Ag biosensor. Figure 6 As can be seen in Figure d, under the same test conditions, the Raman response of Au NSs@Ag nanotag to cTn I was significantly higher than that of other myocardial infarction biomarkers, demonstrating the excellent specificity of the Au NSs@Ag biosensor.

[0076] As shown in Table 1 below, the Au NSs@Ag-based SERS biosensor was compared with the commercial ELISA method, with a relative standard deviation (RSD) of 0.008-0.133% (N=3) and a recovery rate of 79.1%-120%, indicating that the immunosensor has good detection potential in clinical serum samples. The critical standard of the clinical cTn I health value is 0.03 ng / mL. When the serum samples of cases with myocardial infarction risk have a significant difference in cTn I levels with those of healthy people (P<0.05), when the samples below 0.03 ng / mL have no significant difference in cTn I levels with those of healthy people (P>0.05). Therefore, according to the P value, the immunosensor can effectively identify patients at risk of myocardial infarction and meet clinical diagnostic needs.

[0077] Table 1 Concentration, recovery, relative standard deviation and P value of cTn I in clinical samples determined by SERS

[0078]

[0079]

[0080] Note: P values ​​were compared with cTn I concentrations in healthy samples by appropriate statistical tests.

[0081] 5.1.2. Detection of miRNA-133a using AuNSs@Ag SERS substrate

[0082] like Figure 7 As shown in the figure, the detection of miRNA-133a is similar to that of cTn I. As the concentration of miRNA-133a increases from 10 fM to 100 μM, the SERS signal gradually increases and shows a good linear relationship. The detection limit of miRNA can reach the nanometer level. In addition, we detected 6 clinical samples of real MI patients, such as Figure 7 As shown by the blue line in c, it is found that not only the concentration of miRNA-133a shows an excellent linear relationship with the SERS signal, but also the two linear relationship curves obtained in the standard DEPC environment and the real human serum environment are roughly consistent. (Using the Au NSs@Ag SERS biosensor to detect miRNA-133a, in the standard DEPC environment, the concentration of miRNA-133a is linearly related to the SERS intensity (I = 214.32*Log[C miRNA-133a / mol·L -1 ]+2797.59), with a linear correlation coefficient of 0.996 and a LOD of 100 fmol·L -1; In the real human serum environment, the concentration of miRNA-133a and the SERS signal also showed an excellent linear relationship). It is worth noting that the AuNSs@Ag biosensor can achieve highly sensitive detection of miRNA-133a through specific detection. The combined detection of cTn I and miRNA-133a helps to reduce the false positive rate and provides a new basis for establishing a more reliable diagnostic standard for myocardial infarction. At the same time, as shown in Table 2, compared with other reported methods for detecting miRNA, the AuNSs@Ag biosensor prepared in this work has certain biological detection potential.

[0083] Table 2. Detection limits of different miRNA detection methods

[0084]

[0085] 5.2. Study on the sensing mechanism of Au NSs@Ag core-shell structure SERS substrate

[0086] like Figure 8 As shown in the figure, standard samples of AuNSs@Ag-4-MBA and AuNSs@Ag-DTNB were tested under 532nm and 633nm lasers respectively in a standard PBS environment. Although the 532nm laser produced a stronger enhancement effect, its signal-to-noise ratio was poor, which may have a negative impact on ultrasensitive detection. Therefore, 633nm was finally selected as the laser wavelength in the experiment. It is worth noting that in past studies, more and more scholars tend to use 633nm lasers in SERS biological detection. In addition, the results of COMSOL simulation provide strong theoretical support for the SERS effect of Au NSs@Ag.

[0087] COMSOL simulation provides strong support for clarifying the electromagnetic field enhancement mechanism of Au NSs@Ag core-shell materials. First, COMSOL software was used to simulate the AuNSs@Ag material under 532nm laser excitation. Fig. 9 shown. Fig. 9 The simulation results of a show that the maximum electric field intensity can reach 43V / m in the case of a randomly distributed single AuNSs@Ag core-shell structure. However, when multiple AuNSs@Ag materials are close to each other, the electric field intensity will be significantly enhanced due to the formation of local hot spots at the tips of these structures. Fig. 9 b and Fig. 9 In c, it can be clearly observed that the electric field intensity of the Au NSs@Ag material is enhanced, and the maximum electric field intensity is 73.5V / m.

[0088] Then, COMSOL software was used to simulate the Au NSs@Ag material under 633nm laser excitation, as shown in Fig.10shown. Fig.10 The simulation results of a show that the maximum electric field strength can reach 93.9V / m under the randomly distributed single Au NSs@Ag core-shell structure. When multiple Au NSs@Ag materials are close to each other, not only local hot spots are formed at the tips of these structures, but also in the gap between the Au nanostars and the silver shell, due to the strong electromagnetic coupling, the local electromagnetic field is enhanced. Fig.10 b and Fig.10 In c, it can be clearly observed that the electric field intensity of the Au NSs@Ag material is enhanced, and the maximum electric field intensity is 120V / m.

[0089] 5.3. Study on SERS performance of plasmon nanozymes

[0090] Although Au NSs@Ag core-shell SERS biosensor can detect cTn I and miRNA-133a simultaneously, realize mutual calibration and reduce the false positive rate of detection, due to the inherent properties of precious metals, surface precious metal oxidation and agglomeration will occur after a long time of storage, thus reducing the sensitivity of myocardial infarction marker detection and increasing the risk of death of patients. As nanozyme materials have been gradually used in medical detection in recent years, we chose to combine the superior catalytic properties of nanozyme materials with surface enhanced Raman scattering to prepare a highly sensitive detection system.

[0091] 5.3.1. Study on the activity of Au NSs nanozymes and Au NSs@Ag nanozymes

[0092] The Au NSs nanozyme and Au NSs@Ag nanozyme were compared. The Raman reporter molecule 4-MBA was used to detect the gold nanostar particles and the gold nanostar core-shell. Fig.11 As shown in Figure b, it can be seen that the Raman intensity of Au NSs@Ag is higher than that of pure gold nanoparticles due to the gap enhancement of the Raman reporter molecule. Subsequently, we added hydrogen peroxide and TMB to the two materials respectively, and used their peroxidase properties to oxidize the colorless and Raman-inactive TMB into sky blue Raman-active oxTMB. Fig.11 The color changes visible to the naked eye in a and 11b also prove the successful synthesis of the nanozyme activity. Next, we tested the Raman activity of the two nanozyme materials. Fig.11As shown in Figure e, after adding TMB, the gold nanostar has a larger comparative area due to its unique surface structure, and studies have shown that gold nanoparticles have higher nanozyme activity than silver nanoparticles. Therefore, the Raman intensity of Au NSs nanozyme is higher than that of Au NSs@Ag nanozyme, which may be due to the production of more oxTMB. In addition, 3 to 5 points were selected for SERS test in each group of SERS performance tests, and the average value was calculated and the standard error was made. In subsequent experiments, Au NSs nanozyme will be used as the substrate for the design and synthesis of nanozyme materials.

[0093] 5.3.2 Detection of cTn I by Au NSs nanozymes

[0094] The addition of hydrogen peroxide oxidizes the Raman-inactive TMB into oxTMB, which has strong Raman activity and has a peak at 1170 cm -1 , 1349cm -1 , 607cm -1 There is a characteristic peak at the position where cardiac troponin can be detected. Fig.12 As shown in Figure a, although the Au NSs@Ag core-shell structure we prepared can achieve sensitive detection of cTn I, as time goes by, the noble metal nanoparticles undergo oxidation and agglomeration, causing the Raman signal to drop rapidly, thereby reducing the detection sensitivity. After adding hydrogen peroxide and TMB, we can see that the Au NSs nanozyme not only has excellent detection performance but also has super strong detection stability. Fig.12 b It can be seen that although about three weeks have passed, the Raman signal has not dropped significantly. Therefore, AuNSs nanozymes are expected to become a new SERS substrate material for detecting biomarkers.

[0095] Example 2. Preparation of MoO2@Au NSs Nanozyme SERS Substrate and Detection of cTn I

[0096] 2.1 Experimental part

[0097] 2.1.1. Preparation of CeO2

[0098] Mix 300 μL of 0.5 mM K2PtCl4 and 5.0 mL of deionized water in a 20 mL glass bottle. After gently shaking for 2 min at room temperature, take 500 μL of freshly prepared 10 mM Ce(AC)2 solution and 4.2 mL of deionized water, shake gently and add to the above mixture. Next, place the mixture in a 100 ° C water heating box. After 1 hour, collect the precipitate by centrifugation and wash it with deionized water and ethanol 5 times respectively to remove unreacted substances and residual solution. Finally, the sample was dried at 60 ° C overnight to obtain CeO2 powder.

[0099] 2.1.2. Preparation of MoO2

[0100] First, MoS2 nanosheets were synthesized by hydrothermal method. 0.8 mmol of (NH4)6Mo7O 24 ·4H2O and 0.026mol of CH4N2S were added to 40mL of deionized water and then stirred for 10min to completely dissolve at room temperature to obtain a uniform solution. The resulting solution was transferred to a 100mL stainless steel autoclave lined with Teflon and kept at 180°C for 12h. After cooling to room temperature and pouring out the supernatant, the black precipitate was collected by centrifugation and washed with deionized water and ethanol 5 times, respectively. Finally, the sample was dried at 60°C overnight to obtain MoS2 NSs powder. MoO2 was then obtained by calcining at 250°C to 450°C in a tube furnace.

[0101] 2.1.3. Preparation of MnO2

[0102] First, the pH was adjusted to 9.5 using 0.1 mol / L KOH solution, and then 80 μL of 0.01 mol / L KMnO4 solution and 400 μL of 0.01 mol / L K2C2O4 solution were added. Then, it was kept in an ice water bath for 10 minutes, and then heated to 60°C in a water bath and kept for 2 hours. The precipitate was collected by centrifugation and washed 5 times with deionized water and ethanol respectively to remove unreacted substances and residual solution. Finally, the sample was dried at 60°C overnight to obtain MnO2 powder.

[0103] 2.1.4. Preparation of MoO2@Au NSs SERS substrate

[0104] like Fig.13 As shown, 25 mL of deionized water, 2 mL of the previously prepared gold nanosphere seed solution and 25 mg of MoO2 were added to a clean beaker. Under magnetic stirring, 0.5 mL of 0.025 M HAuCl4 and 50 μL of 1 M HCl were added in sequence. After the mixture was stirred for about 3 min, 0.5 mL of 0.002 MAgNO3 and 0.25 mL of 0.1 M ascorbic acid were added. During this process, the color of the solution quickly changed to blue-black. Stirring was continued for about 2 h, and the gold nanoparticles were reduced on the surface of MoO2 by attracting a large number of free electrons on the surface of MoO2, and the gold nanostars were electrostatically adsorbed to its surface by van der Waals forces through long-term mechanical stirring. The preparation methods of gold nanostars loaded with other different transition metal oxides are the same as described above.

[0105] like Fig.14 and 15 As shown, when different substrates are selected for transition metal oxides, their performance varies greatly, and the results show that MoO2 has the best performance.

[0106] 2.1.5. Preparation of nanotags

[0107] The synthesis steps of the nanotag are as follows: First, 140 μL of TMB solution was added to 1.0 mL of MoO2@Au NSs solution. The mixture was vortexed vigorously to ensure thorough mixing and then stored at 4°C overnight. In the second step, 100 μL of 500 μM COOH-PEG-SH solution was added to the mixture and then stirred to ensure uniformity. The resulting mixture was incubated at 4°C overnight. After that, 5 μL of 40 mg / mL EDC solution and 110 mg / mL NHS solution were added respectively to activate the functional groups. After gently stirring the reaction in the dark for 15 minutes, 10 μL of 0.1 mg / mL antibody solution was added and the mixture was incubated at 4°C overnight to promote antibody binding.

[0108] 2.1.6.SERS performance test

[0109] Standard PBS environment test: before the test, add 110μL H2O2 and wait for the solution to quickly turn sky blue. Then, take out 10μL nanotag and 10μL standard PBS antigen samples of different concentrations and drop them into the groove of the slide in turn. React at 37°C for 30 minutes. Finally, use a Raman spectrometer to perform Raman testing using a 633nm laser.

[0110] Human serum environmental test: Before the test, add 110μL H2O2 and wait for the solution to quickly turn sky blue. Then take out 10μL of nano-tags and 10μL of real human serum antigen samples of different concentrations and drop them into the groove of the slide in turn. React at 37°C for 30 minutes, and finally use a Raman spectrometer to perform Raman testing using a 633nm laser.

[0111] XPS characterization is conducive to further observation of the chemical state and elemental composition of the material. The full XPS spectrum shows that MoO2@AuNSs is composed of Mo, O, and Au elements. Fig.16 As shown in b, Mo 6+ 3d 3 / 2 、Mo 5+ 3d 3 / 2 、Mo 6+ 3d 5 / 2 and Mo 5+ 3d 5 / 2 There are corresponding characteristic peaks; Au 4f 7 / 2 and Au 4f 5 / 2 There are two obvious peaks at 84.35 eV and 88.08 eV. In addition, the main oxygen peak can be fitted into three independent peaks, and the binding energies from high to low are 533.48, 531.78, and 529.68 eV, respectively, corresponding to the adsorbed oxygen (O A ), vacancy oxygen (O V ) and lattice oxygen (OL ). The XPS spectrum of MoO2@Au NSs also proves the successful preparation of the material.

[0112] 2.2. Study on the enzyme activity of MoO2@Au NSs nanozymes

[0113] like Fig.17 As shown, in the reaction mechanism of MoO2@Au NSs nanozyme, H2O2 acts as an electron acceptor, producing water by decomposing H2O2, thereby oxidizing colorless tetramethylbenzidine into sky-blue oxidized tetramethylbenzidine. This type of enzymatic color development reaction is usually used in the colorimetric detection of biological molecules.

[0114] Therefore, in order to explore the peroxidase-like activity of MoO2@Au NSs, a typical reaction of catalytic oxidation of TMB in the presence of H2O2 was carried out. Fig.18 As shown in the figure, MoO2@Au NSs can catalyze the decomposition of H2O2, while TMB molecules are oxidized to oxTMB, and the color of the reaction system quickly changes from colorless to blue. The oxidation product oxTMB has a strong absorption peak at 652nm in ultraviolet absorption, and oxTMB has a strong absorption peak at 1170cm in the Raman spectrum. -1 , 1349cm -1 , 607cm -1 There are characteristic peaks at , which indicates that the prepared MoO2@Au NSs nanozyme material has high SERS activity.

[0115] like Fig.19 As shown, the activity of the nanozyme was studied using a Raman laser spectrometer. As the reaction time increases, it can be seen that the solution first changes from colorless to light blue, and then slowly deepens until it remains unchanged. As can be seen from the figure, the Raman intensity gradually increases with time. The reason may be that the increase in reaction time causes the number of TMB molecules in the solution to be oxidized into oxTMB molecules to increase, thereby increasing the Raman intensity. When the reaction proceeds to about 9 minutes, the TMB molecules in the solution have been basically completely oxidized.

[0116] In order to further demonstrate the peroxidase-like activity of MoO2@Au NSs, some comparative experiments were carried out using UV-visible spectrophotometer to study its catalytic performance. Fig. 20 As shown in Figure a, when only MoO2@AuNSs or H2O2 are present in the solution, MoO2@Au NSs can hardly oxidize TMB molecules. Therefore, only when TMB, MoO2@Au NSs and H2O2 are all present, the color of the solution quickly turns to blue, indicating that MoO2@Au NSs has peroxidase mimetic activity.

[0117] Next, the factors affecting the peroxidase activity of MoO2@Au NSs were optimized. Fig. 20 As shown in Figures b-f, the catalytic activity of MoO2@AuNSs increases with the increase of TMB, H2O2 and MoO2@Au NSs concentrations. As the reaction time gradually increases, the catalytic activity of MoO2@Au NSs increases with time.

[0118] Therefore, the optimal conditions for the peroxide activity of MoO2@Au NSs are: 35μL MoO2@Au NSs; 140μL TMB; 110μL H2O2; 100μL sodium acetate buffer; and the optimal reaction time is 9min.

[0119] 2.3. MoO2@Au NSs composites as SERS substrate for detection of cTn I

[0120] The surface morphology and SERS signal uniformity of MoO2@AuNSs were studied. The uniformity of MoO2@AuNSs was studied using laser Raman microscopy. The overall morphology of the MoO2@AuNSs substrate material was relatively uniform and completely consistent with the uniform morphology observed by laser Raman microscopy. Fig.21 The three-dimensional Raman spectrum of b also shows that the SERS signal of MoO2@AuNSs material is uniform and the SERS performance is stable.

[0121] To evaluate the sensitivity of MoO2@AuNSs nanotags, we conducted experiments to detect the myocardial infarction marker cTn I. First, cTnI standard solutions with different concentrations (ranging from 0 to 5 ng / mL) were prepared in a standard phosphate buffered saline (PBS) environment. Fig. 22 a and Fig. 22 As shown in Fig. 2a, the SERS signal gradually increases as the cTn I concentration increases from 0 to 5 ng / mL. It is worth noting that the calculated detection limit is 0.0025 ng / mL. To further quantify this relationship, we fitted a curve between the Raman signal and the cTn I concentration in a standard PBS environment (Fig. Fig. 22 c), the curve equation is I = 593.247*X + 1733.383 (R 2 =0.993). At the same time, clinical samples were tested using serum obtained from patients with myocardial infarction, such as Fig. 22d. It is noteworthy that there is a strong linear correlation between the cTn I antigen concentration and the corresponding SERS signal. It is worth noting that the linear relationship curve obtained in the standard PBS environment is basically consistent with the real serum environment of the patient. These results emphasize the excellent stability and biocompatibility of MoO2@AuNSs nanomaterials, which makes the MoO2@AuNSs SERS sensor have remarkable sensitivity.

[0122] Subsequently, the stability and specificity of MoO2@Au NSs nanotags for cTn I were also tested. First, the Raman intensity of the same Raman tag was tested every two weeks. Fig.23 As shown in a, it can be seen that as time goes by, the MoO2@Au NSs material is oxidized, resulting in a decrease in Raman intensity. However, before 42 days, its Raman intensity did not decrease significantly, and after 56 days, it was found that the Raman intensity decreased significantly, thus affecting its detection sensitivity. In addition, as Fig.23 As shown in Figure b, under the same test conditions, the Raman response of the nanotag to cTn I is significantly higher than that of other different biomarkers, indicating that the MoO2@Au NSs nanozyme biosensor has excellent specificity. At the same time, compared with the detection limits of other detection methods that have been reported (Table 3), the MoO2@AuNSs nanozyme biosensor prepared in this work has a lower detection limit and higher sensitivity.

[0123] Table 3 Comparison of different methods for detecting cTnI using SERS

[0124]

[0125]

[0126] As shown in Table 4, the relative standard deviation (RSD) of the MoO2@Au NSs-based SERS biosensor was compared with the commercial ELISA method, and the recovery rate was 75.3% to 160%, which showed that the immunosensor had good detection potential in clinical serum samples. The critical standard of the clinical cTn I health value was 0.03 ng / mL. When the cTnI level of serum samples with myocardial infarction risk was significantly different from that of healthy people (P<0.05), the cTnI level of samples below 0.03 ng / mL was not significantly different from that of healthy people (P>0.05). Therefore, according to the P value, the immunosensor can effectively identify patients with myocardial infarction risk and meet the clinical diagnosis needs.

[0127] Table 4. Concentration, recovery, relative standard deviation and P value of cTn I in clinical samples determined by SERS

[0128]

[0129] Note: P values ​​were compared with cTn I concentrations in healthy samples by appropriate statistical tests.

[0130] 2.4. Study on the sensing mechanism of MoO2@Au NSs nanozyme composites

[0131] 2.4.1 Study on the catalytic mechanism of MoO2@Au NSs nanozymes

[0132] In order to study the enzyme activity mechanism of MoO2@Au NSs, the Michaelis-Menten equation (1-1) was used to calculate its maximum reaction rate (V max ) and the Michaelis constant (K m ).like Fig.24 As shown in a, the concentration of hydrogen peroxide is kept constant, and different TMB concentrations are adjusted to detect using ultraviolet absorption spectroscopy to calculate a standard curve. Then, the detection record is performed every 5 seconds and the reaction TMB concentration is calculated using the standard curve to calculate the reaction rate, as shown in FIG. Fig.24 b. Finally, Fig.24 c shows that under the premise of keeping the hydrogen peroxide concentration constant, the maximum reaction rate and the Michaelis constant are calculated using the double inverse form of the Michaelis equation (1-2). It can be seen from the figure that the initial reaction rate is positively correlated with the substrate concentration within a certain range. Most importantly, the MoO2@Au NSs nanozyme material has a lower K m When the concentration of hydrogen peroxide was kept constant, the K values ​​of TMB substrates with different concentrations were m The value is 0.658, and the Vmax value is 17.749. When the TMB concentration is kept constant, the K m The value is 1.237 and the Vmax value is 25.491.

[0133]

[0134] More importantly, the maximum reaction rates and Michaelis constants that can be achieved by seven different types of peroxidase-like nanozymes are listed and tabulated, as shown in Table 5. The Michaelis constant refers to the maximum reaction rate (V max ), which means that the larger the Michaelis constant, the more substrate is needed to reach the maximum reaction rate, so K m The smaller the affinity, the faster the enzymatic reaction. Compared with these typical peroxidase-like enzymes, the designed MoO2@Au NSs nanozyme is found to be very competitive, laying a great foundation for the preparation of new nanozymes combined with SERS biosensors.

[0135] Table 5 Michaelis constants and maximum reaction rates of different types of peroxidases

[0136]

[0137] 2.4.2 Study on the SERS enhancement mechanism of MoO2@Au NSs nanozyme composites

[0138] The excellent SERS performance of MoO2@AuNSs nanozyme composites can be attributed to the synergistic effect of electromagnetic field enhancement and chemical enhancement. On the one hand, it comes from the electromagnetic field enhancement effect between particles of MoO2@Au NSs composites, which is similar to the previous COMSOL simulation. On the other hand, as a typical semiconductor material, MoO2 not only exhibits metallic properties, but also has a strong SPR effect due to the presence of a large number of free electrons on the surface. When composited with AuNSs, the enriched electrons on the surface of MoO2 will be injected into the Fermi level of Au, so that the MoO2@AuNSs composite structure reaches a new charge balance. Therefore, the SERS enhancement effect mainly comes from the charge transfer mechanism.

[0139] Although the above description is centered on the embodiment, it is only an example and does not limit the present invention. It is clear to those skilled in the art that various modifications and applications not illustrated above can be made within the scope of the essential characteristics of the present embodiment. For example, each component specifically shown in the embodiment can be implemented after being modified. Moreover, various differences related to such modifications and applications should be interpreted as being included in the scope of the present invention as defined in the attached claims.

[0140] The main sources of reagents and equipment in this example are as follows:

[0141] Table 6 Chemical / biological reagents used in this study

[0142]

[0143]

[0144] Table 7 Experimental instruments and characterization equipment

[0145]

Claims

1. Application of gold-containing nanomaterials as SERS substrates or biosensors for identifying myocardial infarction markers or manufacturing myocardial infarction marker detection equipment / devices, characterized in that: The Au-containing nanomaterial is selected from at least one of the following AF: A. Gold nanostar particles Au NSs; B. AuNSs@Ag core-shell structure of gold nanostar particles coated with silver; C. Transition metal oxide loaded with A or B; D. A, B or C loaded with Raman signal molecules; E. D having antibodies and / or capture probes bound to the surface; F. E bound to antigen and / or miRNA; G. AF activated by oxidation with hydrogen peroxide and TMB.

2. The use according to claim 1, characterized in that: The myocardial infarction marker comprises at least one of cTn I and miRNA-133a.

3. The use according to claim 1, characterized in that: The gold-containing nanomaterial recognizes myocardial infarction markers in an ex vivo serum sample.

4. The use according to claim 1, characterized in that: The preparation method of the gold nanostar particles AuNSs is as follows: add sodium citrate solution to HAuCl4 solution, react until gold nanospheres AuNPs are formed, add water, HAuCl4 and HCl, AgNO3 and ascorbic acid thereto, react until the solution turns blue-black and continue stirring for 10-20 minutes to obtain the desired AuNSs solution.

5. The use according to claim 1, characterized in that: The AuNSs@Ag core-shell structure of the gold nanostar particles coated with silver is synthesized by a seed-mediated method: a gold nanostar particle solution is prepared using a gold nanosphere AuNPs seed solution, and then the silver nanoparticles are reduced to the surface of the gold nanostars using ascorbic acid to prepare AuNSs@Ag.

6. The use according to claim 1, characterized in that: The transition metal oxide is selected from MoO2.

7. The use according to claim 1, characterized in that: The preparation method of the transition metal oxide loaded with A or B is as follows: under stirring, HAuCl4 and HCl, AgNO3 and ascorbic acid are sequentially added to a mixture of a gold nanosphere Au NPs seed solution and MoO2 until the solution turns blue-black, and stirring is continued for 1-3 hours.

8. The use according to claim 1, characterized in that: The loaded Raman signal molecules are selected from 4-MBA and DTNB.

9. The use according to claim 1, characterized in that: The capture probe is an amino-modified capture probe.

10. The use according to claim 1, characterized in that: In the preparation process of AF activated by oxidation with hydrogen peroxide and TMB, the volume ratio of AF, TMB and H2O2 is 1:3-5:2-4, and the reaction time is 5-15 minutes.